Multiple stab incision technique to prevent postoperative acute compartment syndrome of leg in proximal and segmental fracture tibia and fibula: a prospective study - Naik, K. Parthasarathi; S., Shankarlinga; Kyavater, Basavaraj S.; M., Prashanthkumar (International Journal of Research in Orthopaedics, 2022)
The objective is to study the effectiveness of Multiple stab incision technique in preventing acute compartment syndrome (ACS) in proximal and segmental fractures of both bones (Tibia and fibula) in leg. This study is prospective done at K. S. Hospital Koppal, Karnataka spanning for a period of one year (April 2020 to April 2021). A total of 20 patients of both genders aged 20-60 years were included in the study. Multiple stab incision technique was performed in patients after fixation of Tibia by either closed nailing or MIPPO plating. This procedure was done under spinal anesthesia. Multiple stab incision technique significantly decreased the chances of post-op ACS in proximal and segmental fractures of both bones (tibia and fibula) in leg. Multiple stab incision technique is help full in preventing developing compartment syndrome.